(3JdbjM Gdaghe aj JfbjM UjZ GdYehes - (3UdGM GdOjf Ndjd Hf GdYdGFj GdTGaYjs
(3ChdgG (B:s
(3jHOC HGdHGH GdChd ai JMQjQ ePGgH GdYdeGA ai GKHGJ UjZ GdYehe hfajgG heG GSJOd Hg dcd bhd ef Pdc s
(3BNQgG (B:s
(3dCf aJM eKd gPG GdGMJeGd jWQb GdNdd Edi GdGSJOdGd HcKjQ ef GaYGdg Udi Gddg Ydjg hSde hef gPG GjVkG MOjK GHf YeQ QVi Gddg YfgeG Gfg cGf Ydi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Yf fSNI GdeDda hYdjgG NWgs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
Keywords: (3CUhd Gdabgs